Anticipatory threat responses mediate the relationship between mindfulness and anxiety: A cross-sectional study - Xu, Yuanyuan; Huang, Wenqiang; Yan, Xiaofan; Lu, Fang; Li, Min (Frontiers in Public Health, 2022)
Increasing research has shown that mindfulness-based interventions can effectively alleviate anxiety; however, the underlying neural mechanism has not yet been elucidated. Recent studies suggest that abnormal and excessive anticipatory responses to unpredictable threats play an important role in anxiety symptoms. Mindfulness refers to the non-judgmental awareness of the present moment's real experience, which is antithetical to the future-oriented thinking processes involved in anxiety-oriented cognition and its corresponding emotion regulation tactics. Thus, mitigating anticipatory threat responses may be a potential mechanism by which mindfulness alleviates anxiety. This study aimed to detect the possible mediating effects of anticipatory threat responses on the relationship between mindfulness and anxiety. A total of 35 trait-anxious (TA) individuals and 36 low-anxious (LA) individuals were recruited to participate in the predictable and unpredictable threat test. Self-reported intolerance of uncertainty (IU) and electroencephalographic responses to uncertainty were recorded. TA individuals reported more IU and less mindfulness, and exhibited significantly higher late positive potential (LPP) and longer reaction time (RT) than LA individuals in the unpredictable negative threat condition. In addition, there were significant mediating effects of the LPP amplitude and RT in the uncertain threats on the relationship between mindfulness and anxiety. The data from this study verified that mitigating anticipatory threat responses (including self-reported IU, behavioral RT, and LPP amplitude) might be the potential mechanism by which mindfulness alleviates anxiety. These findings may have practical implications for the development and optimization of mindfulness treatments for anxiety.